Coarse-Grained Description of a Brush−Melt Interface in Equilibrium and under Flow - Pastorino, Claudio (2008)
The equilibrium and flow properties of a polymer liquid confined in a brush-coated channel are studied by molecular dynamics simulations using a dissipative particle dynamics (DPD) thermostat. We focus on the regime of high-grafting density, where the brush progressively becomes a stiff and smooth, soft surface and layering of the polymer melt at the brush−melt interface is observed. We use the Gibbs criterion to localize the brush−melt interface and analyze its equilibrium fluctuation in terms of a capillary wave Hamiltonian augmented by an elastic term that accounts for the deformability of the brush. Poiseuille and Couette flows are investigated, and the slip length and location of the hydrodynamic boundary are computed. In the high-grafting regime, the brush roughness decreases and slippage is observed. The results are compared to the effective channel width, which is defined via the integrated flow rate for Poiseuille flow. Evidence of local changes of the near-surface viscosity is provided, and the consistency of the Navier slip boundary condition is investigated.